Морфофункциональные изменения строения репродуктивной системы белых крыс линии Vistar в условиях метаболического синдрома - Нечепоренко, А. Г.; Бушман, В. С.; Necheporenko, A. G.; Bushman, V. S.; Нечепоренко, Альона Геннадіївна; Бушман, Вікторія Сергіївна (My University, 2021)
Пребывание экспериментальной группы животных на высококалорийной диете приводит к формированию метаболического синдрома, а именно гипергликемии, увеличению ИМТ, снижению концентрации ЛПВП, гиперхолестеринемии, гипертриглицеридемии.The stay of the experimental group of animals on a high-calorie diet leads to the formation of a metabolic syndrome, namely hyperglycemia, an increase in BMI, a decrease in the concentration of HDL cholesterol, hypercholesterolemia, and hypertriglyceridemia.
Morphofunctional changes in the structure of the reproductive system of white rats of the Vistar line under metabolic syndrome
Keywords: метаболический синдром; инсулинорезистентность; ожирение; гипергликемия; гиперхолестеринемия; metabolic syndrome; insulin resistance; obesity; hyperglycemia; hypercholesterolemia